2013
DOI: 10.1186/1475-9276-12-33
|View full text |Cite
|
Sign up to set email alerts
|

Social capital in relation to alcohol consumption, smoking, and illicit drug use among adolescents: a cross-sectional study in Sweden

Abstract: BackgroundSocial capital has lately received much attention in public health research. However, few studies have examined the influence of social capital on alcohol consumption, smoking and drug use which have strong influence on public health. The present cross-sectional study investigated whether two measures of social capital were related to substance use in a large population of Swedish adolescents.MethodsA total of 7757 13–18 year old students (participation rate: 78.2%) anonymously completed the Survey o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
56
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 52 publications
3
56
3
Order By: Relevance
“…In contrast with the previous results, Winstanley et al (2008) in USA and Aslund and Nilsson (2013) in Sweden reported that secondary school students in neighbourhoods with low social capital and greater neighbour disorganization were at increased odds of alcohol consumption. It seems plausible that both low and high neighbourhood and community social capital may be associated with increased risk for health damaging behaviours, albeit with a different underlying pathway: in low social capital communities alcohol consumption is an mani festation of the lack of social control and lower community reinforcements of desired behaviours (Aslund & Nilsson, 2013), whereas in high social capital communities, it is a method of socialization. Takakura (2011) reported that the likelihood of alcohol consumption increased 1.5 times among girls with a low level of trust and safety among 3248 students aged 15-18-years-old in the Prefecture of Okinawa, Japan.…”
contrasting
confidence: 99%
“…In contrast with the previous results, Winstanley et al (2008) in USA and Aslund and Nilsson (2013) in Sweden reported that secondary school students in neighbourhoods with low social capital and greater neighbour disorganization were at increased odds of alcohol consumption. It seems plausible that both low and high neighbourhood and community social capital may be associated with increased risk for health damaging behaviours, albeit with a different underlying pathway: in low social capital communities alcohol consumption is an mani festation of the lack of social control and lower community reinforcements of desired behaviours (Aslund & Nilsson, 2013), whereas in high social capital communities, it is a method of socialization. Takakura (2011) reported that the likelihood of alcohol consumption increased 1.5 times among girls with a low level of trust and safety among 3248 students aged 15-18-years-old in the Prefecture of Okinawa, Japan.…”
contrasting
confidence: 99%
“…Nevertheless, multilevel studies of youth health have been limited to social capital in neighbourhoods and communities (De Clercq et al 2012;Thorlindsson et al 2012;Å slund and Nilsson 2013), with possibly little attention paid to school-related issues (Morrow 1999). Students spend most of their daytime hours at school, which can be a particularly important context for setting norms for students' behavioural patterns and attitudes (Johansen et al 2006), and thus might have shared influences on student health and health-related behaviours (West et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Most studies on social capital and smoking have applied proxy measures of social capital such as generalized trust and social participation to examine its link to smoking behavior. These studies have shown that those persons with higher levels of social participation or generalized trust are less likely to smoke 16,17 and more likely to cease smoking. 11 Few studies have examined network social capital and smoking prospectively, and, therefore, less is known about the potential influence of network capital on smoking behavior.…”
mentioning
confidence: 99%